Thromboembolism in Patients with Cancer: A Practical Guide to Recurrent Events - Sergey Kozhukhov; Nataliia Dovganych (Reviews in Cardiovascular Medicine)
Cancer patients have an increased risk of venous thromboembolism (VTE), and VTE is the second most common cause of death among them. Anticoagulation plays a key role in the treatment of cancer-associated thrombosis (CAT). Low-molecular-weight heparin (LMWH) or direct oral anticoagulants (DOACs) are effective and generally safe options for cancer-associated VTE. However, those patients have a 10–20% risk of VTE recurrence in spite of using anticoagulants. The main reasons for recurrent VTE (rVTE) can be non-compliance, inadequate dosing of anticoagulants, thrombocytopenia and malignancy progression. Despite the publication of major guidelines regarding the management of CAT, the treatment of patients with rVTE is undefined. Treatment options for rVTE include bridging to LMWH in cases of oral anticoagulants use, LMWH dose escalation, and sometimes considering inserting a vena cava filter. This review paper summarizes the management of cancer-associated VTE, risk factors for rVTE and the treatment algorithm of rVTE.